Adult Children of High-Conflict Marriages - Donna Davis (EDIS, 2012)
“Most of us have probably heard someone declare that they had remained in their marriage 'for the sake of the kids.' Research suggests, however, that logic may not hold up. In the long run, children whose parents are in high-conflict marriages may not be any better off than children whose parents divorce. While divorce has been shown to create significant negative outcomes for many children over the course of their lives, new research shows that conflict in marriage can have lasting effects into adulthood as well.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.